Magnetic Field Induced Changes in the Shoot and Root Proteome of Barley (Hordeum vulgare L.) - Shabrangy, Azita (Front Plant Sci, 2021)
The geomagnetic field (GMF) has been present since the beginning of plant evolution. Recently, some researchers have focused their efforts on employing magnetic fields (MFs) higher than GMF to improve the seed germination, growth, and harvest of agriculturally important crop plants, as the use of MFs is an inexpensive and environment-friendly technique. In this study, we have employed different treatments of MF at 7 mT (milliTesla) at different time points of exposure, including 1, 3, and 6 h. The extended exposure was followed by five consecutive days at 6 h per day in barley seeds. The results showed a positive impact of MF on growth characteristics for 5-day-old seedlings, including seed germination rate, root and shoot length, and biomass weight. Furthermore, ~5 days of delay of flowering in pre-treated plants was also observed. We used a shotgun proteomics approach to identify changes in the protein signatures of root and shoot tissues under MF effects. In total, we have identified 2,896 proteins. Thirty-eight proteins in the shoot and 15 proteins in the root showed significant changes under the MF effect. Proteins involved in primary metabolic pathways were increased in contrast to proteins with a metal ion binding function, proteins that contain iron ions in their structure, and proteins involved in electron transfer chain, which were all decreased significantly in the treated tissues. The upregulated proteins' overall biological processes included carbohydrate metabolic process, oxidation-reduction process, and cell redox homeostasis, while down-regulated processes included translation and protein refolding. In general, shoot response was more affected by MF effect than root tissue, leading to the identification of 41 shoot specific proteins. This study provides an initial insight into the proteome regulation response to MF during barley's seedling stage.